2004
DOI: 10.1111/j.1365-2141.2004.04840.x
|View full text |Cite
|
Sign up to set email alerts
|

Podocalyxin in human haematopoietic cells

Abstract: Summary Podocalyxin‐like protein (PCLP) is a sialomucin‐type membrane protein structurally related to CD34 and endoglycan. It was first described in glomerular podocytes and endothelial cells. In mice, PCLP is present in haemangioblasts, and in both chicken and mice it is a marker of early haematopoietic stem cells and lineage‐restricted haematopoietic progenitors. Its expression decreases during differentiation of haematopoietic cells. Of mature blood cells, only chicken and rat thrombocytes express PCLP prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 37 publications
(51 reference statements)
3
43
0
Order By: Relevance
“…Macrophage colonystimulating factor modulates the development of hematopoiesis by stimulating the differentiation of PCLP1 + CD45 -cells to endothelial cells in the AGM region. In humans, previous studies suggested that PCLP1 may be a useful marker for a subset of hematopoietic stem cells (Kerosuo et al, 2004). Here, we developed a monoclonal antibody against extracellular region of human PCLP1 (hPCLP1), termed 53D11.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Macrophage colonystimulating factor modulates the development of hematopoiesis by stimulating the differentiation of PCLP1 + CD45 -cells to endothelial cells in the AGM region. In humans, previous studies suggested that PCLP1 may be a useful marker for a subset of hematopoietic stem cells (Kerosuo et al, 2004). Here, we developed a monoclonal antibody against extracellular region of human PCLP1 (hPCLP1), termed 53D11.…”
Section: Discussionmentioning
confidence: 99%
“…2A). In addition, 53D11 was found to react to endogenous hPCLP1 expressed on MCF-7, a breast carcinoma cell line, which has been proved to express PCLP1 (Kerosuo et al, 2004;Somasiri et al, 2004) (Fig. 2B).…”
Section: Production Of Antibodies Against Human Pclp1 Expressed On Thmentioning
confidence: 99%
See 1 more Smart Citation
“…PODXL has also been found in vascular endothelium, lung, brain, multipotent hematopoietic precursors, megakaryocytes and platelets [4,14,15], as well as in several types of tumors in which the expression levels appear to correlate with the metastatic capacity [16,17,18]. However, unlike the role of PODXL in the renal homeostasis, almost nothing is known about its physiological role in extrarenal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies used podocalyxin as the marker of choice in identifying podocytes, but their specificity was hampered because this protein is expressed also on endothelial cells, parietal epithelial cells, and a variety of nonrenal cells, such as platelets and hematopoietic stem cells. [74][75][76][77] Markers of the podocyte slit diaphragm, ie, nephrin and podocin, as well as the cytoskeletal protein synaptopodin, are known to be downregulated in diabetic nephropathy, 78 perhaps signifying shedding of these cells in the urine, rendering them a reasonable urinary marker. The sensitivity of podocyturia, as identified by nephrin for diagnosis, was demonstrated when urinary nephrin (nephrinuria) was found in a substantial number of normoalbuminuric patients, in addition to microalbuminuric and normoalbuminuric patients.…”
Section: Podocyte Markersmentioning
confidence: 99%